Analisis Implementasi Etika Jual Beli Kopi Dalam Islam di Desa Koto Rami Kecamatan Lembah Masurai Kabupaten Merangin - Habriyanto Habriyanto; Bambang Kurniawan; Heri Paliza (BADAN PENERBIT STIEPARI PRESS, 2024)
The purpose of this research is to find out how Islamic business ethics in Koto Rami Village, Lembah Masurai District, Merangin Regency, to find out whether business ethics in Koto Rami Village, Lembah Masurai District, Merangin Regency are in accordance with Islam, to find out what are the obstacles in implementing Islamic business ethics in the village. Koto Rami, Lembah Masurai District, Merangin Regency. This research is field in nature. The data collection techniques in this research are: observation, interviews, and documentation carried out by the coffee shop and coffee farmers. Then the existing data was analyzed using qualitative analysis. As for the research results, it was found that Islamic business ethics were carried out by the toke and farmers, toke who cheat by reducing the scale, coffee farmers mix coffee beans that still have a lot of water content with dry coffee beans, do not explain the actual condition of the goods so that it harms other people, there are still many toke who badmouth other toke with the motive of business competition , many farmers slander other farmers so that they don't buy the farmer's harvest. Analysis of the implementation of Islamic business ethics in Koto Rami Village, Lembah Masurai District, Merangin Regency is not in accordance with the principles of business ethics.